Derrida and Lacan : another writing - Lewis, Michael, 1977- (Edinburgh University Press, 2008)
Derrida and Lacan: Another Writing argues that Jacques Derrida's philosophical understanding of language should be supplemented by Jacques Lacan's psychoanalytic approach to the symbolic order. Lacan adopts a non-philosophical, genetic or developmental approach to the question of language and in doing so isolates a dimension that Derrida cannot properly envisage: the imaginary. Michael Lewis argues that the real must be understood not just in relation to the symbolic but also in relation to the imaginary. The existence of an alternative approach to the real that is other than language allows us to identify the idiosyncrasies of Derrida's purely transcendental approach, an approach that addresses language in terms of its conditions of possibility. Lacan shows us that an attention to the genesis of the symbolic order of language and culture should lead us to understand this real other in a different way. This book relates transcendental thought to the insights of non-philosophical thought, and, more specifically, it proposes a way in which philosophy might relate to the insights of the human and natural sciences. By critically juxtaposing Derrida and Lacan, Derrida and Lacan: Another Writing attempts to systematise Slavoj ÅưiÅℓek's presentation of a Lacanian alternative to Derridean deconstruction. This work should be of interest to all readers in continental thought and transcendental philosophy, deconstruction, psychoanalysis, and literary studies.
Keywords: Derrida, Jacques.; Lacan, Jacques, -- 1901-1981.; Derrida, Jacques; Lacan, Jacques, -- 1901-1981; Philosophy, French.; Philosophie française.; PHILOSOPHY -- History & Surveys -- Modern.; PHILOSOPHY -- Movements -- Deconstruction.; Philosophy, French; Electronic books.